Histone demethylases in chromatin biology and beyond - Dimitrova, E; Turberfield, A; Klose, R (EMBO Press, 2015)
Histone methylation plays fundamental roles in regulating chromatin‐based processes. With the discovery of histone demethylases over a decade ago, it is now clear that histone methylation is dynamically regulated to shape the epigenome and regulate important nuclear processes including transcription, cell cycle control and DNA repair. In addition, recent observations suggest that these enzymes could also have functions beyond their originally proposed role as histone demethylases. In this review, we focus on recent advances in our understanding of the molecular mechanisms that underpin the role of histone demethylases in a wide variety of normal cellular processes.